Full-Day School in Sorong of West Papua (Study at Al-Izzah Integrated Islamic Primary School in Sorong City) - Sukman S; Hermanto Hermanto (International Journal of Multi Discipline Science, 2019)
Full-day School is a learning system by emphasizing to students to be more in school with all existing activities and emphasizes on various educational activities so that students will be more able to explore themselves. With this system is able to shape the character of students by giving or planting moral and religiosity values. In 2016, the full-day school system was announced by the Indonesian Minister of Education and Culture, Mr. Muhajir Efendi and raised the pros and cons for its implementation. Al Izzah Integrated Islamic Primary School in Sorong City West Papua is a leading and favorite private primary school in Sorong City, West Papua, which has been implementing a full-day school system, starting from 2006 until now. The full-day school system implemented by Al Izzah Integrated Islamic Primary School in Sorong City is different from other schools, the time is to go home late in the afternoon but the concept of implementation is different. Full-day school of Al Izzah Integrated Islamic Primary School in Sorong City refers to the Curriculum of the Integrated Islamic School Network. The system is used because the program needs a lot of time. This is a qualitative descriptive research. The primary data source comes from the Chairperson of the Al-Izzah Foundation, the principal, teachers, and students of Al-Izzah Integrated Islamic Primary School in Sorong City. The data collection techniques that are used is observation, interview, and documentation. The data are analyzed by Miles and Huberman method. Student output with the application of a full-day school system at Al Izzah Integrated Islamic Primary School in Sorong City, namely tartil students reading the Qur'an and memorizing at least 2 Juz Al-Qur'an, 5 values in the field of study are complete, dhuha and dhuhur prayers in congregation with awareness, dedicated to parents/teachers, good social behavior, love environment, and independence. The output includes the characters of Al Izzah Integrated Islamic Primary School students who have character, achievement, and independence.